Interlayer correlations versus intralayer correlations in a Quantum Hall bilayer at total filling one - Moller, G; Simon, S (2005)
In Quantum Hall bilayers, at total filling factor one, a transition from a compressible phase with weak interlayer correlations to an incompressible phase with strong interlayer correlations is observed as the distance between the two layers is reduced. The transition between these two regimes can be understood using a trial wavefunction approach based on the composite particle picture. © EDP Sciences.